Bài 1 Giải phương trình
a) √x-2√x-1=√x-1-1
b)√4-2√3=x-1
Bài 2 Giải phương trình
A) √25x^2=x-12
B)√x^2-2x+1=3x+2
Bài 3 Giải phương trình
A) √(-2x)^2=4
B)√x^2-2x+1= |-3|
C)√4x^2+4x+1=2
D)√3x^2= |-√6|
Bài 4 Giải phương trình
A) 4x^2-4√3x+3
B) x^2 +4√5x+20=0
C)√x^4=4
D)√√x^4=7
Bài 5 Giải phương trình
A) |2x-1|=1-2x
B)|3x+2|=3x+2
C)√9x^2-6x+1=3x-1
D)√4x^2-12x+9=3-2x
Bài 6 Giải phương trình
A) √25x^2-3x-2=0
B)√(-3x)^2+x-1=0
C)√x^2-10x+25=x+4
D) √x^2+12x+36=2x+5
Đáp án:
$\begin{array}{l}
1)a)\sqrt {x – 2\sqrt {x – 1} } = \sqrt {x – 1} – 1\\
\left( {dkxd:x \ge 1} \right)\\
\Rightarrow \sqrt {x – 1 – 2\sqrt {x – 1} + 1} = \sqrt {x – 1} – 1\\
\Rightarrow \sqrt {{{\left( {\sqrt {x – 1} – 1} \right)}^2}} = \sqrt {x – 1} – 1\\
\Rightarrow \left| {\sqrt {x – 1} – 1} \right| = \sqrt {x – 1} – 1\\
\Rightarrow \sqrt {x – 1} – 1 \ge 0\\
\Rightarrow \sqrt {x – 1} \ge 1\\
\Rightarrow x \ge 2\\
b)\sqrt {4 – 2\sqrt 3 } = x – 1\\
\Rightarrow \sqrt {{{\left( {\sqrt 3 – 1} \right)}^2}} = x – 1\\
\Rightarrow \sqrt 3 – 1 = x – 1\\
\Rightarrow x = \sqrt 3 \\
2)a)\sqrt {25{x^2}} = x – 12\left( {dkxd:x \ge 12} \right)\\
\Rightarrow \left| {5x} \right| = x – 12\\
\Rightarrow \left[ \begin{array}{l}
5x = x – 12\\
5x = – x + 12
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = – 3\left( {ktm} \right)\\
x = 2\left( {ktm} \right)
\end{array} \right.\\
\Rightarrow x \in \emptyset \\
b)\sqrt {{x^2} – 2x + 1} = 3x + 2\left( {dk:x \ge – \dfrac{2}{3}} \right)\\
\Rightarrow \sqrt {{{\left( {x – 1} \right)}^2}} = 3x + 2\\
\Rightarrow \left| {x – 1} \right| = 3x + 2\\
\Rightarrow \left[ \begin{array}{l}
x – 1 = 3x + 2\\
x – 1 = – 3x – 2
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = – \dfrac{3}{2}\left( {ktm} \right)\\
x = – \dfrac{1}{4}\left( {tmdk} \right)
\end{array} \right.\\
Vay\,x = – \dfrac{1}{4}\\
3)a)\sqrt {{{\left( { – 2x} \right)}^2}} = 4\\
\Rightarrow \left[ \begin{array}{l}
– 2x = 2\\
– 2x = – 2
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = 1\\
x = – 1
\end{array} \right.\\
b)\sqrt {{x^2} – 2x + 1} = \left| { – 3} \right|\\
\Rightarrow {x^2} – 2x + 1 = 9\\
\Rightarrow {x^2} – 2x – 8 = 0\\
\Rightarrow \left( {x – 4} \right)\left( {x + 2} \right) = 0\\
\Rightarrow \left[ \begin{array}{l}
x = 4\\
x = – 2
\end{array} \right.\\
c)\sqrt {4{x^2} + 4x + 1} = 2\\
\Rightarrow \left| {2x + 1} \right| = 2\\
\Rightarrow \left[ \begin{array}{l}
2x + 1 = 2\\
2x + 1 = – 2
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = \dfrac{1}{2}\\
x = – \dfrac{3}{2}
\end{array} \right.\\
d)\sqrt {3{x^2}} = \left| { – \sqrt 6 } \right|\\
\Rightarrow \left[ \begin{array}{l}
\sqrt 3 x = \sqrt 6 \\
\sqrt 3 x = – \sqrt 6
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = \sqrt 2 \\
x = – \sqrt 2
\end{array} \right.\\
4)a)4{x^2} – 4\sqrt 3 x + 3 = 0\\
\Rightarrow {\left( {2x – \sqrt 3 } \right)^2} = 0\\
\Rightarrow x = \dfrac{{\sqrt 3 }}{2}
\end{array}$
$\begin{array}{l}
b){x^2} + 4\sqrt 5 x + 20 = 0\\
\Rightarrow {\left( {x + 2\sqrt 5 } \right)^2} = 0\\
\Rightarrow x = – 2\sqrt 5 \\
c)\sqrt {{x^4}} = 4\\
\Rightarrow {x^2} = 2\\
\Rightarrow \left[ \begin{array}{l}
x = \sqrt 2 \\
x = – \sqrt 2
\end{array} \right.\\
5)a)\left| {2x – 1} \right| = 1 – 2x\\
\Rightarrow 2x – 1 \le 0\\
\Rightarrow x \le \dfrac{1}{2}\\
b)\left| {3x + 2} \right| = 3x + 2\\
\Rightarrow 3x + 2 \ge 0\\
\Rightarrow x \ge – \dfrac{2}{3}\\
c)\sqrt {9{x^2} – 6x + 1} = 3x – 1\\
\Rightarrow \left| {3x – 1} \right| = 3x – 1\\
\Rightarrow 3x – 1 \ge 0\\
\Rightarrow x \ge \dfrac{1}{3}\\
d)\sqrt {4{x^2} – 12x + 9} = 3 – 2x\\
\Rightarrow \left| {2x – 3} \right| = 3 – 2x\\
\Rightarrow 2x – 3 \le 0\\
\Rightarrow x \le \dfrac{3}{2}\\
6)a)\sqrt {25{x^2}} – 3x – 2 = 0\\
\Rightarrow \left| {5x} \right| = 3x + 2\left( {dk:x \ge – \dfrac{2}{3}} \right)\\
\Rightarrow \left[ \begin{array}{l}
5x = 3x + 2\\
5x = – 3x – 2
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = 1\left( {tm} \right)\\
x = – \dfrac{1}{4}\left( {tm} \right)
\end{array} \right.\\
b)\sqrt {{{\left( { – 3x} \right)}^2}} + x – 1 = 0\\
\Rightarrow \left| {3x} \right| = 1 – x\left( {x \le 1} \right)\\
\Rightarrow \left[ \begin{array}{l}
3x = 1 – x\\
3x = x – 1
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = \dfrac{1}{4}\left( {tmdk} \right)\\
x = – \dfrac{1}{2}\left( {tmdk} \right)
\end{array} \right.\\
c)\sqrt {{x^2} – 10x + 25} = x + 4\left( {x \ge 4} \right)\\
\Rightarrow \left| {x – 5} \right| = x + 4\\
\Rightarrow x – 5 = – x – 4\\
\Rightarrow x = \dfrac{1}{2}\left( {ktm} \right)\\
d)\sqrt {{x^2} + 12x + 36} = 2x + 5\left( {x \ge – \dfrac{5}{2}} \right)\\
\Rightarrow \left| {x + 6} \right| = 2x + 5\\
\Rightarrow \left[ \begin{array}{l}
x + 6 = 2x + 5\\
x + 6 = – 2x – 5
\end{array} \right.\\
\Rightarrow \left[ \begin{array}{l}
x = 1\left( {tm} \right)\\
x = \dfrac{{ – 11}}{3}\left( {ktm} \right)
\end{array} \right.
\end{array}$